QUR’ANIC PERCEPTION OF MONOTHEISM AND GOD'S ABSOLUTE IMPARTIALITY (IN THE LIGHT OF MAULANA ABU AL-KALAM AZAD’S WRITINGS) - Hasballah Thaib, Assistant Professor Zamakhsyari bin; Shamsud, Professor Dr Salahuddin Bin Mohd (IJRDO - Journal of Social Science and Humanities Research, 2023)
Abu al-Kalam Azad studied some historical facts that he dealt with in his book (Interpretation of al-Qur’an) and (Umm al-Kitab) but he did not ignore Darwin’s theory of ascension that everything grows slowly from the bottom up, except for the religious belief. Its matter is completely different because it descended from the top to the bottom and retreated from the best to the worst. Azad mentioned that God Almighty created all people as one nation, then people differed into various sects, meaning that the oldest human belief is the doctrine of monotheism. Azad tried to prove that most religions called people to monotheism, and the dispute among them resulted from internal contradictions. He believed that the dispute among the religions centers on depicting divine attributes, and there is no difference among them in the same deity. He did not try to call the people to the unity of religions - as it seems - but he wanted to call them to the unity of faith, which is the monotheism. The best form of monotheism for him is Islam, as stated in the Qur’an: (No doubt that the religion of God is Islam), (and any religion will not be accepted (Āl-ʻImrān: 19-85). Therefore, Azad called all people to Islam in an indirect way, he emphasized that what was the perception of worshiping God in the sixth century AD in the world was in need for the Qur’an to be revealed to correct the crookedness and corruption in the man’s religious thought.